Exploiting real-world data to monitor physical activity in patients with osteoarthritis: the opportunity of digital epidemiology. Issue 2 (February 2022) - Ravalli, Silvia; Roggio, Federico; Lauretta, Giovanni; Di Rosa, Michelino; D'Amico, Agata Grazia; D'agata, Velia; Maugeri, Grazia; Musumeci, Giuseppe
Abstract: Osteoarthritis is a degenerative joint disease that affects millions of people worldwide. Current guidelines emphasize the importance of regular physical activity as a preventive measure against disease progression and as a valuable strategy for pain and functionality management. Despite this, most patients with osteoarthritis are inactive. Modern technological advances have led to the implementation of digital devices, such as wearables and smartphones, showing new opportunities for healthcare professionals and researchers to monitor physical activity and therefore engage patients in daily exercising. Additionally, digital devices have emerged as a promising tool for improving frequent health data collection, disease monitoring, and supporting public health surveillance. The leveraging of digital data has laid the foundation for developing a new concept of epidemiological study, known as "Digital Epidemiology". Analyzing real-world data can change the way we observe human behavior and suggest health interventions, as in the case of physical exercise and osteoarthritic patients. Furthermore, large-scale data could contribute to personalized and precision medicine in the future. Herein, an overview of recent clinical applications of wearables for monitoring physical activity in patients with osteoarthritis and the benefits of exploiting real-world data in the context of digital epidemiology are discussed. Abstract : Physical activity, Osteoarthritis, Digital epidemiology, Digital devices, Exercise.